2023
DOI: 10.3389/fmed.2023.1214108
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and mechanical stretch in the developing lung: risk factors for neonatal and pediatric lung disease

Abstract: Chronic airway diseases, such as wheezing and asthma, remain significant sources of morbidity and mortality in the pediatric population. This is especially true for preterm infants who are impacted both by immature pulmonary development as well as disproportionate exposure to perinatal insults that may increase the risk of developing airway disease. Chronic pediatric airway disease is characterized by alterations in airway structure (remodeling) and function (increased airway hyperresponsiveness), similar to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 209 publications
0
2
0
Order By: Relevance
“…In our recent in vitro study using human fetal ASM, we showed clock gene expression sensitivity to O 2 such that O 2 may indeed be altering the clock (Bartman et al., 2021 ). Clinically, when neonates are administered supplemental O 2 , they experience shifts in O 2 saturation leading to intermittent hypoxia‐hyperoxia (Zhang et al., 2023 ). It is therefore important to consider not only the percentage of oxygen in experimental studies, but also the timing (e.g., chronic versus intermittent) and cyclicity of it as well.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent in vitro study using human fetal ASM, we showed clock gene expression sensitivity to O 2 such that O 2 may indeed be altering the clock (Bartman et al., 2021 ). Clinically, when neonates are administered supplemental O 2 , they experience shifts in O 2 saturation leading to intermittent hypoxia‐hyperoxia (Zhang et al., 2023 ). It is therefore important to consider not only the percentage of oxygen in experimental studies, but also the timing (e.g., chronic versus intermittent) and cyclicity of it as well.…”
Section: Discussionmentioning
confidence: 99%
“…117 There are, however, legitimate concerns regarding the impact of long-term continuous distending pressure on the developing lung. 247 The utility of routine extension of CPAP until 32 weeks PMA or 1250g versus gradual weaning from CPAP to HFNC will be tested objectively in a clinical trial that is currently recruiting patients (NCT05557139). Information from this study may help further inform NRS practices used beyond 7 days of life.…”
Section: Evolving Course: Dol 7 -36 Weeks Pma -Maintain Growth Trajec...mentioning
confidence: 99%